Analisis Perlakuan Akuntansi Atas Aset Tetap Pada Cv. Anggie Jaya Bersama - Putri Dwi Nida; Maulan Irwandi; Andini Utari Putri (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to examine the accounting treatment of fixed assets at CV. Anggie Jaya Together. Types of data used are primary and secondary data obtained from interviews with directors, treasurers, and company historical reports. The method used is descriptive qualitative. The results showed that the distribution of assets carried out by CV. Anggie Jaya Bersama regarding its fixed assets is not in line with PSAK no. 16. Furthermore, in recording fixed assets CV. Anggie Jaya Bersama does not yet know its economic age so it can be concluded that there is no problem with this classification because it is following the accounting standards based on PSAK 16. However, it was found that in the process of recording and presenting fixed assets the company had not adjusted to the PSAK No. 16.